The Bloomsbury handbook of Japanese religions - Baffelli, Erica 1976-; Rambelli, Fabio 1963-; Castiglio, Andrea (Bloomsbury Academic, 2021)
"Providing an overview of current cutting-edge research in the field of Japanese religions, this Handbook is the most up-to-date guide to contemporary scholarship in the field. As well as charting innovative research taking place, this book also points to new directions for future research, covering both the modern and pre-modern periods. Edited by Erica Baffelli, Andrea Castiglioni, and Fabio Rambelli, The Bloomsbury Handbook of Japanese Religions includes essays by international scholars from the USA, Europe, Japan, and New Zealand. Topics and themes include gender, politics, the arts, economy, media, globalization, and colonialism. The Bloomsbury Handbook of Japanese Religions is an essential reference point for upper-level students and scholars of Japanese religions as well as Japanese Studies more broadly."
Includes bibliographical references and index
Chaplaincy and spiritual care / Kasai Kenta -- Cultural heritage / Lindsey DeWitt -- Disasters / Levi McLaughlin -- Economy and spirituality / Ioannis Gaitanidis -- Economy of Buddhism / Jørn Borup -- Case study. Buddhist temples of the future / Paulina K. Kolata -- Empire and colonialism / Emily Anderson -- Case study. Aesthetics of Buddhist modernism / Paride Stortini -- Environmentalism / Aike P. Rots -- Case study. Grassroots environmental activities in Risshō Kōseikai / Aura di Febo -- Food offerings / Allan G. Grapard -- Folk performing arts / Suzuki Masataka -- Gender / Kawahashi Noriko -- Globalization / Richard Payne -- Case study. Diaspora Buddhism / Jørn Borup -- Islam / Komura Akiko -- Law / Mark Mullins -- Materiality / Halle O'Neal -- Media and technology / Kaitlyn Ugoretz and Erica Baffelli -- Case study. World-wide Shinto : the globalization of 'Japanese' religion / Kaitlyn Ugoretz -- Case study. Robots / Kimura Takeshi -- Medicine / Katja Triplett -- Minorities / Takahashi Norihito -- Case study Daijō Islam (Mahayāna Islam) / Komura Akiko -- "New religions" / Kato Masato -- Pilgrimages and "sacred" geography / Ian Reader -- Politics / Ōmi Toshihiro -- Case study. Religion, socialism, and secularization / James Mark Shields -- Premodern traditions / Hayashi Makoto -- Sexuality / Ori Porath -- Sound / Ōuchi Fumi -- Case study. The matsuri as sonic event / Andrea Giolai -- Space / Tatsuma Padoan -- Spiritualism and occultism / Yoshinaga Shin'ichi -- Spirituality / Horie Norichika -- Tourism / Yamanaka Hiroshi -- Women / Emily Simpson -- Case study. Mountain worship and women / Kobayashi Naoko
Keywords: Buddhism / bicssc; Religion; Japan -- Religion; Japan -- Religious life and customs; Japan